Anatomical and mechanical properties of swine midpalatal suture in the premaxillary, maxillary, and palatine region - Fabio Savoldi; Bing Xu; James K. H. Tsoi; Corrado Paganelli; Jukka P. Matinlinna (Scientific Reports, 2018)
Abstract The mechanical properties of the midpalatal suture and their relationship with anatomical parameters are relevant for both tissue engineering and clinical treatments, such as in sutural distraction osteogenesis. Soft tissues were dissected from ten swine heads and the hard palate was sliced perpendicularly to the midpalatal suture. Thirteen specimens were collected from each animal and analysed with micro-computed tomography and 4-point-bending for sutural width (Sw), interdigitation (LII), obliteration (LOI), failure stress (σ f ), elastic modulus (E), and bone mineral density (BMD). Values of the premaxillary, maxillary, and palatine region were compared with Kruskal-Wallis one-way ANOVA and Spearman’s rank coefficient was used to analyse the correlation between parameters and their position along the suture (α = 0.05). LII had values of 1.0, 2.9, and 4.3, LOI had values of 0.0%, 2.5%, and 4.5%, and E had values of 12.5 MPa, 31.3 MPa, and 98.5 MPa, in the premaxillary, maxillary, and palatine region, respectively (p < 0.05). Failure stress and rigidity of the midpalatal suture increased from rostral to caudal, due to greater interdigitation and obliteration. These anatomical and mechanical findings contribute to characterise maxillary growth, and may help to understand its mechanical reaction during loading, and in virtual simulations.